The Fibonacci Array

Calculus Level 5

1 1 + 1 1 + 2 1 + 3 1 + 5 1 + . . . + 1 2 + 1 4 + 2 8 + 3 16 + 5 32 + . . . + 1 3 + 1 9 + 2 27 + 3 81 + 5 243 + . . . + 1 4 + 1 16 + 2 64 + 3 256 + 5 1024 + . . . + 1 5 + 1 25 + 2 125 + 3 625 + 5 3125 + . . . + . . . + . . . + . . . + . . . + . . . + . . . + . . . + . . . + . . . + . . . + . . . + . . . \begin {array}{ccccccccccc} & \color{#D61F06}{\frac{1}{1}} & + & \color{#D61F06}{\frac{1}{1}} & + & \color{#D61F06}{\frac{2}{1}} & + & \color{#D61F06}{\frac{3}{1}} & + & \color{#D61F06}{\frac{5}{1}} &+& ... \\ + & \color{#D61F06}{\frac{1}{2}} & + & \frac{1}{4} & + & \frac{2}{8} & + & \frac{3}{16} & + & \frac{5}{32} &+& ... \\ + & \color{#D61F06}{\frac{1}{3}} & + & \frac{1}{9} & + & \frac{2}{27} & + & \frac{3}{81} & + & \frac{5}{243} & +&... \\ + & \color{#D61F06}{\frac{1}{4}} & + & \frac{1}{16} & + & \frac{2}{64} & + & \frac{3}{256} & + & \frac{5}{1024} &+& ... \\ + & \color{#D61F06}{\frac{1}{5}} & + & \frac{1}{25} & + & \frac{2}{125} & + & \frac{3}{625} & + & \frac{5}{3125} & +& ... \\ + & \color{#D61F06}{...} &+& ... &+& ... &+& ... &+& ... & +&...\\ {+} & \color{#D61F06}{...} &+& ... &+& ... &+& ... &+& ... & +&... \end {array}

The sum above as shown diverges. However, when the column and row in red is removed, the sum converges to A A . Find 1 0 5 A \lfloor 10^{5} A \rfloor .

Details:

  1. Both the columns and rows extend to infinity.
  2. In each row, the numerators are the terms of the Fibonacci sequence, while the denominators are the successive powers of the row number.
  3. In each column, the numerators are the same, and the denominators are terms of the form k n k^n , n n being kept constant every column, and k k is a positive integer corresponding to the row number of the term.


The answer is 216522.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

Denoting by F n F_n , the n n th Fibonacci number , note that we can write the sum as S = k 2 n 2 F n k n = k 2 n 2 ϕ n ( 1 ϕ ) n 2 ϕ 1 S=\sum_{k\ge 2}\sum_{n\ge 2}\frac{F_n}{k^n}\\=\sum_{k\ge 2}\sum_{n\ge 2}\frac{\phi^n-(1-\phi)^n}{2\phi-1} where ϕ = 1 + 5 2 \phi=\frac{1+\sqrt{5}}{2} , is the golden ratio. Then, noting that 1 < ϕ < 2 1<\phi<2 , we can simplify the sum as ( 2 ϕ 1 ) S = n 2 k 2 ( ϕ n k n ( 1 ϕ ) n k n ) = k 2 ( ( ϕ / k ) 2 1 ϕ / k ( ( 1 ϕ ) / k ) 2 1 ( 1 ϕ ) / k ) = ϕ k 2 ( 1 k ϕ 1 k ) ( 1 ϕ ) k 2 ( 1 k 1 + ϕ 1 k ) (2\phi-1)S=\sum_{n\ge 2}\sum_{k\ge 2}\left(\frac{\phi^n}{k^n}-\frac{(1-\phi)^n}{k^n}\right)\\=\sum_{k\ge 2}\left(\frac{(\phi/k)^2}{1-\phi/k}-\frac{((1-\phi)/k)^2}{1-(1-\phi)/k}\right)\\=\phi\sum_{k\ge 2}\left(\frac{1}{k-\phi}-\frac{1}{k}\right)-(1-\phi)\sum_{k\ge 2}\left(\frac{1}{k-1+\phi}-\frac{1}{k}\right) Now, the digamma function satisfies the following property: ψ ( x + 1 ) = γ + k 1 ( 1 k 1 x + k ) \psi(x+1)=-\gamma+\sum_{k\ge 1}\left(\frac{1}{k}-\frac{1}{x+k}\right) where γ \gamma is the Euler-Mascheroni constant. Then, it follows after a little bit of mainipulation, S = ( 1 ϕ ) ψ ( ϕ ) ϕ ψ ( 1 ϕ ) 2 ϕ 1 γ + 2 S=\frac{(1-\phi)\psi(\phi)-\phi\psi(1-\phi)}{2\phi-1}-\gamma+2 We can further simplify the expression using the reflection formula satisfied by ψ ( ) \psi(\cdot) ψ ( 1 x ) ψ ( x ) = π cot ( π x ) \psi(1-x)-\psi(x)=\pi\cot(\pi x) to obtain S = 2 γ + π ( ϕ 1 ) cot ( π ϕ ) 2 ϕ 1 ψ ( 1 ϕ ) S=2-\gamma+\frac{\pi(\phi-1)\cot (\pi \phi)}{2\phi-1}-\psi(1-\phi) which evaluates to 2.16522 \approx 2.16522 . Thus the answer is 216522 \boxed{216522} .

Efren Medallo
Sep 14, 2016

Define S S such that

S = 1 x + 1 x 2 + 2 x 3 + 3 x 4 + 5 x 5 + . . . S = \frac{1}{x} + \frac{1}{x^2} + \frac {2}{x^3} + \frac{3}{x^4} + \frac {5}{x^5} + ...

so

S x = 1 x 2 + 1 x 3 + 2 x 4 + 3 x 5 + 5 x 6 + . . . \frac{S}{x} = \frac{1}{x^2} + \frac{1}{x^3} + \frac {2}{x^4} + \frac{3}{x^5} + \frac {5}{x^6} + ...

Subtract the two and we get

S S x = 1 x + 1 x 2 ( 1 x + 1 x 2 + 2 x 3 + 3 x 4 + 5 x 5 + . . . ) S - \frac {S}{x} = \frac{1}{x} + \frac{1}{x^2} ( \frac{1}{x} + \frac{1}{x^2} + \frac {2}{x^3} + \frac{3}{x^4} + \frac {5}{x^5} + ... )

S S x = 1 x + S x 2 S - \frac {S}{x} = \frac{1}{x} + \frac{S}{x^2}

Multiplying x 2 x^2 on both sides,

x 2 S x S = x + S x^2S - xS = x + S

so

S = x x 2 x 1 S = \frac{x}{x^2 - x - 1}

The array above can now be condensed to

x = 1 x x 2 x 1 \large \sum_{x=1}^{\infty} \frac{x}{x^2 - x - 1}

which, by the way, diverges. Note: I'm sorry I cannot give an in depth explanation to this as I am not very well versed with the different series convergence tests available. However, on an intuitive notion, we can see that the first row (the one in red) consists of plainly infinite 1s (which means this will blow up to infinity), while the first column is the famous divergent series n = 1 1 n \sum_{n=1}^{\infty} \frac{1}{n} . Since these two take part in the array in question, then it can be said that this array series indeed diverges.

So, to make for adjustments by removing the divergent parts, we get

x = 2 x x 2 x 1 1 x \large \sum_{x=2}^{\infty} \frac{x}{x^2 - x - 1} - \frac{1}{x}

We now start at x = 2 x =2 because the first row (where x = 1 x=1 ) is removed, and the subtracted expression takes into account the removal of the first column.

I'll stop here for now.

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...